슈퍼커패시터용 그래핀볼 - 그래핀옥사이드 복합전극의 전기화학적 특성 - 정우준(Woo-Jun Jeong); 오예찬(Ye-Chan Oh); 김상호(Sang-Ho Kim) (Biuletyn Uniejowski, 2020)
Composite material of the graphene ball (GB) inserted graphene oxide (GO) sheet for a supercapacitor electrode was studied. Chemical vapor deposition (CVD) process used to make GBs on the silicon oxide nanoparticles. The GBs mixed into the GO sheets to make GOGB and reduced it to create a reduced GOGB(RGOGB) composite. The RGOGB composite electrode had a large surface area and improved electrochemical properties. Specific capacitance of the RGBGO composite electrode was higher over 20 times than a pure GO and GOGB electrode in cyclic voltammetry(CV) tests, and the Z' and Z" impedance measured by an electrochemical impedance spectrometry(EIS) also low. So, the RGBGO composite electrode would use effectively to expand a performance of supercapacitor.